Regulation of digital advertising in Morocco: challenges of digital sovereignty, economic impacts and societal prospects in 2025 - Hamza EL HAMDAOUI; Abdelmjid EL HAMDAOUI (African Scientific Journal, 2025)
Abstract This paper will discuss the inception of a specific regulatory framework for digital advertising in Morocco in 2025. In an environment where international platforms (Google, Meta, TikTok, YouTube) dominate more than 80% of digital advertising investments, the absence of clear national legislation relates to questions of digital sovereignty, transparency, and consumer protection. This article will engage in a discussion of the context of this legal reform, its major drivers, and the effects the new law might have on digital marketing stakeholders, advertisers, local agencies, foreign platforms, and users. In the framework of a literature review and analysis of institutional debates, this article will articulate some of the major challenges of digital advertising regulation, and will also reflect on its potential role in the development of a more competitive, equitable digital environment in Morocco. Keywords : Digital Advertising, Regulation, Digital Marketing, International Platforms, Digital Sovereignty.